KAJIAN PEMBUATAN BUMBU SERBUK ”BUBBOR PADDAS” INSTAN MENGGUNAKAN METODE FOAM-MAT DRYING - Andi Maryam; Rozana; Angga Tritisari; Junardi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The seasoning powder of "Bubbor Paddas" is formulated using local ingredients from the Sambas region of West Kalimantan with the foam-mat drying method. "Bubbor Paddas" is a typical Sambas Malay porridge made from various vegetables and spices. The instant seasoning for "Bubbor Paddas" that has been developed so far has been in the form of impractical paste seasoning in packaging and has a short shelf life, reaching only two months. This research aims to find a powdered seasoning formula for "Bubbor Paddas" that is more practical in packaging and serving and has a longer shelf life. The research includes two formulations, namely the use of white egg foaming agent and Tween-80. The parameters observed are the percentage of water content and free fatty acids tested periodically over 35 days with testing on the 7th, 14th, 21st, 28th, and 35th days. The research results showed that the quality of kesum paste and powder seasoning could still be maintained until the 35th day of storage. The highest levels of free fatty acids in kesum paste and powder were 0.3363% and 0.3199% respectively. This free fatty acid content value still meets the required threshold for free fatty acids in oil, namely a maximum of 5%. The use of a foaming agent that can speed up the drying process of kesum paste spice into powdered kesum spice is Tween 80 at 0.5%.